Thanking Expressions in Kurdish Language - SABRI ALI, DR. SHERZAD; OTHMAN, AYADFAYZALLAH (Journal of Duhok University, 2019)
Thanking is one of the most important verb of speech act in pragmatics. The present research entitled “Thanking Expressions in Kurdish Language” aims at investigating thanking expressions in Bahdenan area and preferred strategies used in certain occasions. The researcher adopted descriptive analytical approach and used statistic to reach the ratio of each strategy. The main aim of the present research is to specify the most preferred strategy used by the speakers and to specify the percentage of each strategy. The researcher has come up with many findings. The research consists introduction and two chapters. The first chapter deals with thanking and pragmatics and it contains the definition of thanking, its relation to pragmatics and thanking strategies. The second chapter deals with thanking expressions in Kurdish language.